2019
DOI: 10.32674/jis.v9i3.746
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and Supervising International Students in School Counseling Programs

Abstract: Graduate counseling programs in the United States have increased their population of international students. However, limited studies have addressed the challenges of international students, specifically in school counseling programs. Considering the cultural disparities that exist for international school counseling students and the challenges associated with being an international student in general, this article identifies and delineates a culturally appropriate mentoring and supervision model that has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…The report also indicated that about 1% of master’s students in CACREP accredited counseling programs were international students. Numerous studies have reported the challenges international students encounter in their academic environment, which influences their academic achievements and psychological well-being (Asempapa, 2019 ; Boafo-Arthur, 2014 ; Yoon & Portman, 2004 ).…”
Section: Internationalization Of the Counseling Programmentioning
confidence: 99%
See 2 more Smart Citations
“…The report also indicated that about 1% of master’s students in CACREP accredited counseling programs were international students. Numerous studies have reported the challenges international students encounter in their academic environment, which influences their academic achievements and psychological well-being (Asempapa, 2019 ; Boafo-Arthur, 2014 ; Yoon & Portman, 2004 ).…”
Section: Internationalization Of the Counseling Programmentioning
confidence: 99%
“…During the acculturation process, international students may experience several barriers that adversely affect their social and academic communications participation. Asempapa ( 2019 ) asserts that these experiences result in increased acculturative stress during international students’ field experience.…”
Section: Challenges Of International Counseling Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite facing significant challenges, limited attention has been given to ICSs, including their field experience (Asempapa, 2019;Ng, 2006;Park et al, 2017). Counseling programs require students to take field experience courses to receive supervision while working with real clients (Council for Accreditation of Counseling and Related Educational Programs [CACREP], 2016).…”
mentioning
confidence: 99%
“…Li et al, 2018;McKinley, 2019;Woo et al, 2015;Zhou et al, 2019). Mentorship of international students in specific counseling programs also has been broached (Asempapa, 2019).…”
mentioning
confidence: 99%